BUSINESS STRATEGY FORMULATING FOR SMALL MEDIUM ENTERPRISE GROWTH (CASE STUDY IN HELLIKOPI) (The Indonesian Journal of Business Administration, 2019)
Hellikopi is a micro scale business located in Bandung, Gegerkalong Hilir area. Hellikopi is a small coffee shop that sells drinks such as coffee and other soft drinks. The challenges faced by Hellikopi was to achieve its growing goals in the coffee business often hampered due to the decline in the center of competitiveness caused by the market share of saturated premium coffee and the rapid growth of the premium coffee business, which has the potential to decrease the hellikopi market share. This research was conducted to create a business strategy for Hellikopi in order to increase its competitiveness with both old and new competitors.The current issue faced by the hellikopi is that there is no strategy or plan to be able to compete or develop in an industry that is very competitive, especially the internal problems of the Hellikopi organization which often lead to management errors, especially in terms of financial records which result in a significant imbalance of net income with net income by recording financial assets. This could threaten the operation of the hellikopi so that over time the hellikopi will bankrupt and close if the business issue not immediately resolved.The purpose of this research is to be able to formulate a strategy to the solution of the problems faced by the hellikopi. By using internal analysis and external analysis using interview data, survey data, sources from the internet researchers can formulate SWOT analysis so that researcher can find each SWOT element in the hellikopi so that researchers can find the root of the problem faced by the hellikopi. After finding the root of the problem faced by hellikopi, the researcher continuing the SWOT analysis to the next stage that was TOWS analysis so that researchers can formulate the right strategy for hellikopi use based on the SWOT component owned by the hellikopi so the output strategy formulated by this study is product and service quality control (ST2 ), new collaborative products or services (ST1), utilization of digital platforms (WO1 & SO1), utilization of online motorcycle taxi platforms (WO2), creating a collaborative push culture (SO2), creating effective organizations (WO3) Keywords: Small Medium Enterprises, Five Stage of Small Business Growth, Restructuring Organization, Coffeeshop, Creative Economy